Multiple objective optimization of hydro-thermal systems using Ritz's method - Arnáu L. Bayón (Mathematical Problems in Engineering, 1999)
This paper examines the applicability of the Ritz method to multi-objective optimization of hydro-thermal systems. The algorithm proposed is aimed to minimize an objective functional that incorporates the cost of energy losses, the conventional fuel cost and the production of atmospheric emissions such as <mtext>NO</mtext> x and <mtext>SO</mtext> 2 caused by the operation of fossil-fueled thermal generation. The formulation includes a general layout of hydro-plants that may form multi-chains of reservoir network. Time-delays are included and the electric network is considered by using the active power balance equation. The volume of water discharge for each hydro-plant is a given constant amount from the optimization interval. The generic minimization algorithm, which is not difficult to construct on the basis of the Ritz method, has certain advantages in comparison with the conventional methods.